Reform or reorganization constructing and implementing the new Chinese civil service. - Guobin Zhu (1995)
For more than a decade China has been in the throes of reforming its management and personnel system. With the proclamation of the first general law concerning the civil service entitled `Provisional Regulations Concerning Government Officials', which came into effect on 1 October 1993, this reform is indeed achieving its first objective. How has this new civil service been set up? How was the implementation of the new civil service programmed? These are some of the many questions being asked by close observers of political developments in China. In this article the author attempts to reply to such questions based on his study of the first general law concerning Chinese civil servants
Keywords: Bureaucracy - China; Civil service reform - China; Civil service - China